APPLICATION OF PROPHETIC PARENTING IN MAINTAINING FAMILY RESILIENCE: A THEMATIC AND CONTEXTUAL HADITH APPROACH - Chalimatus Sa’dijah; Khaerul Umam (Edukasi Islami : Jurnal Pendidikan Islam, 2026)
The family resilience in the contemporary era faces various challenges, such as increasing domestic conflict, communication crises, and the weakening role of parents in parenting. This phenomenon demonstrates the importance of presenting parenting patterns that are not only adaptive but also rooted in Islamic values. In this context, prophetic parenting becomes relevant as an alternative approach in fostering family resilience. This study aims to analyze the concept and application of prophetic parenting from the perspective of the hadith, and contextualize it in modern family life. This research method uses a qualitative literature-based study with a thematic and contextual hadith approach. The main data sources are hadiths related to childcare, which are then analyzed using takhrij techniques, thematic classification, and contextual interpretation according to contemporary social realities. The results show that prophetic parenting encompasses several main principles, namely role models (uswah hasanah), love (rahmah), dialogic communication, halal sustenance, and the instilling of tauhid and moral values ​​from an early age. This article concludes that the application of prophetic parenting contributes significantly to strengthening family resilience and serves as a preventative measure against the emergence of unhealthy parenting patterns. The implications of this study underscore the importance of integrating prophetic values into parenting practices—such as using rewards and corrective measures that serve an educational purpose—as the foundation for building a family characterized by sakinah, mawaddah, and rahmah.